2017
DOI: 10.1177/2158244017725794
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflict and Employee Commitment: The Moderating Effect of Perceived Managerial Support

Abstract: This study aimed at investigating the relationship between work-family conflict (work-to-family conflict [WFC] and family-to-work conflict [FWC]) and employee commitment (EC) in banking institution in Kenya. Furthermore, the study focused on exploring the moderating effect of perceived managerial support (PMS) on the relationship between work-family conflict and EC. This study was a cross-sectional survey of 334 employees working in banking institutions where data were collected using self-reported questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
4
25
2
1
Order By: Relevance
“…The findings of Mukanzi and Senaji (2017) supported this position by revealing that work-family conflict had a positive relationship with affective commitment (AC), continuance commitment (CC), and normative commitment (NC). Other studies have also shown that there is a connection between work-life policies and employees commitment in terms of affective, continuance, and normative commitment (Farid, et al, 2014;Diraviam, 2016;Mwangi et al, 2017;Arop, Owan, & Ibor, 2019).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The findings of Mukanzi and Senaji (2017) supported this position by revealing that work-family conflict had a positive relationship with affective commitment (AC), continuance commitment (CC), and normative commitment (NC). Other studies have also shown that there is a connection between work-life policies and employees commitment in terms of affective, continuance, and normative commitment (Farid, et al, 2014;Diraviam, 2016;Mwangi et al, 2017;Arop, Owan, & Ibor, 2019).…”
Section: Introductionmentioning
confidence: 76%
“…Studies have made efforts to address this issue in different parts of the world including Nigeria (Abdullah, Almadhoun, & Ling, 2015;Aleke et al, 2015;Maina, 2016;Diraviam, 2016;Aliakbari & Amoli, 2016;Rao, 2017;Mukanzi & Senaji, 2017;Iman & Wayan, 2018;Arop, Ekpang, & Owan, 2018;Nguru & Gichuhi, 2018;Owan, Arop, & Agunwa, 2019). These studies have used several independent variables in an attempt to address the issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees who prioritize their role in the family, see their role in work as a disturbing thing. In the context of OC, when the role in the family is more important, the goals and values of employees with the goals and values of the organization, are no longer in line, the affective commitment of employees will decrease (Mukanzi & Senaji, 2017).…”
Section: The Effect Of Work-family Conflict (Wfc) On Organizational Cmentioning
confidence: 99%
“…Role in work and family is one of the most important choices and decisions in human life (Mukanzi & Senaji, 2017). In eastern countries like Indonesia, the family is the most important community in one's life (Hofstede, 2002).…”
Section: Structural Modelmentioning
confidence: 99%